2013
DOI: 10.1371/journal.pmed.1001561
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Non-Physician Clinicians and Industry: A Systematic Review

Abstract: In a systematic review of studies of interactions between non-physician clinicians and industry, Quinn Grundy and colleagues found that many of the issues identified for physicians' industry interactions exist for non-physician clinicians. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 44 publications
1
49
0
2
Order By: Relevance
“…Registered nurses described financial relationships with industry that took place outside their workplace that were similar to those reported by colleagues who were physicians or prescribing nurses (12,(21)(22)(23)). Yet, nurses reported that the most significant interactions with industry occurred in day-today practice, both because these interactions were frequently necessary to their practice and because they found them practically and ethically challenging.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Registered nurses described financial relationships with industry that took place outside their workplace that were similar to those reported by colleagues who were physicians or prescribing nurses (12,(21)(22)(23)). Yet, nurses reported that the most significant interactions with industry occurred in day-today practice, both because these interactions were frequently necessary to their practice and because they found them practically and ethically challenging.…”
Section: Discussionsupporting
confidence: 53%
“…Both actual and perceived COIs may threaten nurses' status as the most trusted professionals in the eyes of the public and may jeopardize their relationships with patients (10). Yet, almost nothing is known about the ways that RNs interact with industry, though research suggests they may have become an important "soft target" for industry and a back door to prescribers in light of increasing restrictions on physician-industry interactions (11,12). This has been accompanied by a shift within the medical industry away from traditional marketing channels targeted at physicians, including a reduction in face-to-face marketing and an increase in marketing directed at nonphysician clinicians, payers, and patients (13).…”
mentioning
confidence: 99%
“…Donohue and Berndt (Donohue & Berndt, 2004) found that drug choice probability positively increases with an increase in detailing expenses. Physician detailing has a significant and lasting influence on a physician's drug choice (Iizuka & Jin, 2007, Søndergaard, Vach, Kragstrup, & Andersen, 2009, Grundy, Bero, & Malone, 2013. Manchanda and Chintagunta (2004) reported that physicians who were over-detailed prescribed 50% more than the average physician, while physicians who were optimally detailed prescribed 60-104% more.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Una revisión sistemática publicada en 2013 en Plos Medicine puso de relieve que las interacciones entre industria y profesional afectan también a profesionales sanitarios no médicos 15 . En dicha revisión sistemática se citan de forma específica a los/las dietistas, los cuales mantienen, a pesar de ser conscientes de los problemas relacionados con los sesgos en las investigaciones, actitudes positivas hacia la interacción con la industria, denominándola a veces de forma cariñosa como "el diablo necesario" 15 .…”
unclassified
“…Una revisión sistemática publicada en 2013 en Plos Medicine puso de relieve que las interacciones entre industria y profesional afectan también a profesionales sanitarios no médicos 15 . En dicha revisión sistemática se citan de forma específica a los/las dietistas, los cuales mantienen, a pesar de ser conscientes de los problemas relacionados con los sesgos en las investigaciones, actitudes positivas hacia la interacción con la industria, denominándola a veces de forma cariñosa como "el diablo necesario" 15 . A pesar de que la interacción industria-profesional no es sinónimo de mala praxis en investigación o en la práctica clínica, los datos sobre su influencia en las conclusiones de los estudios son claros y contribuyen a la percepción de que "la ciencia de la nutrición humana y dietética está en venta" 6 .…”
unclassified